The Validity of the Pop-Up Book Media on Puberty Topics for Sixth Grade Elementary School - Viana Sari, Dina; Kusmariyatni, Nyoman (International Journal of Elementary Education, 2020)
This research is based on the limitations of the material in student books and the lack of use of media in the learning process. This study aimed at developing a pop-up book media on the topic of puberty class VI in elementary school. The implementation of this research referred to the procedure of the development model which consisted of the Analyze, Design, Development, Implementation, and Evaluation stages. The subject of this research was the pop-up book media, while the object in this study was the validity of the pop-up book media. Data collection in this study used a questionnaire method. To determine the validity of the pop-up book media, a rating scale instrument was used in the form of an assessment sheet given to four experts. The validation data was then analyzed using the mean formula to find out the average score of the validity of the pop-up book media. The analysis showed the average score of validation of pop-up book media is 4.86 with very good qualifications. This media can be used in the learning process. The teacher will be helped in delivering the material and students can understand the material and take an active role in learning.